Strategi UMKM dalam meningkatkan pendapatan dimasa pandemi Covid-19 guna mempertahankan kelangsungan usaha di era revolusi industri 4.0 (studi pada UMKM makanan dan minuman di Kabupaten Pasuruan) - Sularsih, Hermi; Nasir, Akhamad (Jurnal Paradigma Ekonomika, 2021)
The purpose of this research is to find a strategy to increase MSME income during the COVID-19 pandemic to maintain business continuity in the era of the Industrial Revolution 4.0. The general goal is to increase the knowledge of MSME actors during the COVID-19 pandemic and increase the income of small and medium enterprises (MSMEs) for business continuity in Pasuruan Regency in the era of the Industrial Revolution 4.0. The method used in this study is a qualitative method using descriptive techniques, such as data reduction, data presentation, and concluding SWOT analysis. Informants in this survey are the Office of Cooperatives and Micro Enterprises and SMEs in Pasuruan Regency. The results showed that the Matrix Internal Factors (IFAS) and External Factors (EFAS) showed that MSMEs in the food and beverage business were located in cell V in identification, segment growth, investment choice, and specialization. The strategy that micro food and beverage businesses must be carried out in Pasuruan Regency to increase income to maintain their business in the face of the 4.0 industrial revolution. During the covid 19 pandemic, namely, on Strength Opportunity (SO), strategies used strength to take advantage of external opportunities were created. Â 